(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The fusion of physical and digital resources used to collect, retrieve, analyses, store, produce, and transfer information is known as information and communications technology (ICT). ICT is sometimes used as a longer synonym for information technology (IT), although its use is in some ways broader. ICT is often used to refer to a larger range of forms and kinds of data and communication. This research focused on ICT and its many benefits, including its use in education. ICT have altered how we engage with one other, get the information we need, work, do business, deal with the government, and manage our social life. ICT has made it possible for enterprises to be automated, enabling customers to reach a website or voicemail seven days a week. The development of information and communication technology has resulted in notable developments and improvements in a variety of sectors.